Correlation of the Presence of Parasites in Soil and Nutritional Status of Children Aged 3 to 5 at Purok 15 Barangay Tigatto, Buhangin, Davao City - Babiera, Jemaica Marie A.; Batiancila, Kezia Erica L.; Quilaquil, Tricia Mae S.; Silguera, Junelle P. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
his study aimed to determine the correlation between the presence of parasites in soil and the nutritional status of children aged 3 to 5 at Purok 15 Barangay Tigatto, Buhangin, Davao City. The research design was descriptive and correlational. The researchers gathered the weight and height of children aged 3 to 5 in Purok 15 of Barangay Tigatto, Davao City. Researchers identified the collected soil samples using a systematic sampling technique. Further, the study used Cobb's method to decant and sieve for detecting parasites. The weight and height were calculated to get the BMI. The mean and standard deviation were used to evaluate the nutritional status of the children and the level of parasites. Furthermore, Pearson r was used to determine the relationship between soil-transmitted helminths and the nutritional status of children aged 3 to 5. Results showed that out of 25 samples, 32% of soil samples got positive results with an infectious parasite (Strongyloides stercoralis), while 68% of soil samples were negative from the parasite. Participants' weight (kgs) and height (cm) are normal. In line with this, the BMI of both male and female participants is normal. Also, results showed that the level of the parasites is very low. Moreover, the relationship between the soil-transmitted helminths did not significantly influence the nutritional status of children aged 3 to 5. In conclusion, the soil-transmitted helminths do not affect the nutritional status of children aged 3 to 5. Hence, other factors may influence the nutritional status of children aged 3 to 5. Moreover, since the relationship between STH and the nutritional status of children is not significant, the presence or absence of STH in the latrine area does not affect the nutritional status of children under 3 to 5 years old. Thus, immediate action toward STH elimination could prevent the production of more parasites that could lead to a parasite-free environment.